Single Application of A2 NTX, a Botulinum Toxin A2 Subunit, Prevents Chronic Pain Over Long Periods in Both Diabetic and Spinal Cord Injury-Induced Neuropathic Pain Models - Lin Ma; Jun Nagai; Yuki Sekino; Yoshitaka Goto; Shinji Nakahira; Hiroshi Ueda (Elsevier, 2012)
Botulinum toxin type A is a unique candidate for inhibition of pain transmission. In the present study we attempted to see the beneficial actions of A2 neurotoxin (NTX), an active subunit of botulinum toxin type A. Intraplantar injection of A2 NTX significantly suppressed mechanical allodynia and hypersensitivities to A-fiber stimuli in the diabetic neuropathic pain model. Spinal application of A2 NTX also showed a potent suppression of thermal hyperalgesia and mechanical allodynia in the spinal cord injury-induced neuropathic pain model. A2 NTX seems to be a long-lasting treatment for diabetic and spinal cord injury-induced neuropathic pain. Keywords:: botulinum toxin type A, A2 neurotoxin (NTX), neuropathic pain